Da fala à escrita: marcas da oralidade na rede social do WhatsApp - Menezes, Raimundo da Silva (2024)
This study investigates contemporary linguistic dynamics in social media interactions, with an emphasis on WhatsApp. The object of the investigation is the complex digital literacy and oral practices present on this platform. It explores how such interactions influence and reflect contemporary linguistic dynamics, challenging established linguistic norms. Incorporating the research hypothesis, we seek to examine the role of social networks, especially WhatsApp, in the evolution of contemporary digital language, including changes in structure, vocabulary and grammar, and how these changes challenge linguistic norms and promote interaction between Orality and Written in the Brazilian context. Highlighting the social and educational importance associated with understanding literacy and oral practices in the digital scenario, this investigation aims to analyze the distinct characteristics of speech and writing in WhatsApp interactions, exploring how these digital literacy and oral practices challenge established language standards. The general objective is to investigate contemporary linguistic dynamics in interactions on the WhatsApp social network. Specific objectives include researching and differentiating the characteristics of speech and writing in these interactions. The methodology adopts the qualitative approach proposed by Gil (2008), with ethical data collection and detailed textual analysis to explore the complexities of linguistic interactions on social networks. The results revealed trends of linguistic variation in WhatsApp and insights into perceptions of linguistic 'error' among users. These findings deepen the understanding of contemporary linguistic dynamics and have practical implications for the teaching of the Portuguese language and Brazilian linguistic identity. In summary, the study adopts an exploratory approach, investigating the interrelationship between orality, literacy and linguistic prejudice in the digital environment to enrich the understanding of contemporary linguistic practices.